2018
DOI: 10.3390/rs10101541
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Areas Vulnerable to Sand Encroachment Using Remote Sensing and GIS Techniques in Nouakchott, Mauritania

Abstract: Sand dune advances poses a major threat to inhabitants and local authorities in the area of Nouakchott, Mauritania. Despite efforts to control dune mobility, accurate and adequate local studies are still needed to tackle sand encroachment. We have developed a Sand Dune Encroachment Vulnerability Index (SDEVI) to assess Nouakchott’s vulnerability to sand dune encroachment. Said index is based on the geo-physical characteristics of the area (wind direction and intensity, slope and surface height, land use, veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Africa (Malaki et al, 2009;Afrasinei et al, 2018 ;Gómez et al, 2018) and other arid, and semiarid regions around the world (Mirmousavi, 2016;Baumgertel et al, 2019), which indicate that wind erosion vulnerability increase from north to south, refereeing to the effect of related factors which encourage wind erosion-human impact, degrades soil structure, denudation of natural vegetation, extent of sandy soils, and harsh climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Africa (Malaki et al, 2009;Afrasinei et al, 2018 ;Gómez et al, 2018) and other arid, and semiarid regions around the world (Mirmousavi, 2016;Baumgertel et al, 2019), which indicate that wind erosion vulnerability increase from north to south, refereeing to the effect of related factors which encourage wind erosion-human impact, degrades soil structure, denudation of natural vegetation, extent of sandy soils, and harsh climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that there is another approach toward measuring surface erosion that uses another InSAR product, the so-called phase coherence, rather than the phase angle as shown in Liu et al (2001). With the installment of contemporary InSAR assets such as Terra SAR X, Advanced Land Observing Satellite (ALOS) Phased Array type L-band Synthetic Aperture Radar (PALSAR) 1/2, and Sentinel-1, which have better resolution, revisiting times, and resolving power on the baseline conditions, nowadays some research has begun to establish methods of monitoring sand dune dynamics and eolian migrations as shown in Gaber et al (2018), Gómez et al (2018), and Havivi et al (2018). A detailed study of phase coherence behaviors in arid deserts which may involve eolian erosions was reported by Ullmann et al (2019) who showed that surface characteristics such as slope and wetness are not crucial for the loss of phase coherence, the so-called decorrelation.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers use fixation to face this natural hazardous. There are several sand dune stabilization strategies such as mechanical stabilization, or biological stabilization, presently biological strategies considered as the most common and most efficient strategies (Gómez et al, 2018). Yao et al (2007) utilized multi-temporal Landsat imagery for tracking of dune migration and pattern identification on the northern Alxa plateau, Inner Mongolia, China (Els et al, 2015).…”
Section: Introductionmentioning
confidence: 99%